Biodiversity of woody species in oak woodlands of southern Spain and northern Morocco (Forest Ecology and Management, 1999)
Three biodiversity parameters ± species richness, endemic species richness and taxonomic singularity ± have been evaluated for the woody understorey of oak woodlands on sandstone-derived substrates, on both sides of the Strait of Gibraltar. There is a similarity in ¯oristic composition and ecological distribution of woody plant communities across the Strait. Nevertheless, we have detected signi®cant differences. These include a general reduction in species richness, number of endemic species and taxonomic singularity (at the community level), and a greater abundance of widespread, generalist species, on the southern side (Moroccan) communities, as compared to the north (Spanish ones). We interpret these differences as partly caused by the contrasting management of woodlands, with higher slashing and browsing pressure in Morocco.